Colonies and workers' settlements in the memories of the Germens in Lodz - Kucner, Monika (Acta Universitatis Lodziensis. Folia Germanica, 2017)
This article presents an image of Lodz colonies and workers' settlements in the memories of the Germens in Lodz. They perform a variety of functions: residential, commercial, they are a place of work and leisure. They satisfy also higher needs: they are a part of the cultural and social life. In terms of ethnicity they are places where penetrate different cultures and religions. What particularly distinguishes these areas and giving them specific climate is mostly emotional aspect resulting from the attachment to this place. Their inhabitants form stable communities, with their own customs and traditions. Described by the Germans colonies and workers settlements in the nineteenth and early twentieth century were an integral part of Lodz.